2007
DOI: 10.1002/syn.20437
|View full text |Cite
|
Sign up to set email alerts
|

Responding for brain stimulation reward in the bed nucleus of the stria terminalis in alcohol‐preferring rats following alcohol and amphetamine pretreatments

Abstract: The bed nucleus of the stria terminalis (BNST) has been reported to release increased levels of extracellular dopamine (DA) following the systemic administration of abused drugs in outbred rats. This study examined the BNST as a novel locus for supporting operant responding for brain stimulation reward (BSR) in rats bred for alcohol preference while determining any potentiating effects of ethanol (EtOH) (0.125-1.25 g/kg, i.p.) and amphetamine (0.25-1.60 mg/kg, i.p.) on BSR within the BNST. Also examined was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…This interpretation is based on a model of reward perception in which the effects of alcohol and electrical brain stimulation on mesocorticolimbic activity sum to increase the total amount of positive reinforcement experienced as the mice respond for a given stimulation frequency. This finding replicates earlier studies in rats, where alcohol administration directly lowered BSR thresholds (Eiler et al, 2007; Lewis and June, 1994; Moolten and Kornetsky, 1990) and is consistent with chronic exposure studies that find elevated BSR thresholds upon the removal of alcohol from dependent rats (Rylkova et al, 2008; Schulteis et al, 1995). In the current study, 0.6 g/kg alcohol lowered BSR threshold by approximately 20% in both C57 and DBA mice, an effect that occurred in the first 15 minutes after administration and was not significant in either strain at later time points.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This interpretation is based on a model of reward perception in which the effects of alcohol and electrical brain stimulation on mesocorticolimbic activity sum to increase the total amount of positive reinforcement experienced as the mice respond for a given stimulation frequency. This finding replicates earlier studies in rats, where alcohol administration directly lowered BSR thresholds (Eiler et al, 2007; Lewis and June, 1994; Moolten and Kornetsky, 1990) and is consistent with chronic exposure studies that find elevated BSR thresholds upon the removal of alcohol from dependent rats (Rylkova et al, 2008; Schulteis et al, 1995). In the current study, 0.6 g/kg alcohol lowered BSR threshold by approximately 20% in both C57 and DBA mice, an effect that occurred in the first 15 minutes after administration and was not significant in either strain at later time points.…”
Section: Discussionsupporting
confidence: 91%
“…Early studies (e.g., Vrtunski et al, 1973) relied solely on maximal response rates as the behavioral index of reward and suggested that alcohol can increase responding for BSR. More recent studies reveal that self- or experimenter-administered alcohol can lower BSR thresholds without changing response rates, indicating a potentiation of brain reward circuitry (Eiler et al, 2007; Lewis and June, 1994; Moolten and Kornetsky, 1990). Others have found increases or no effect on stimulation thresholds (Carlson and Lydic, 1976; Ghosh et al, 1991; Schaefer and Michael, 1987).…”
mentioning
confidence: 99%
“…Additionally, while the group mean data revealed no significant differences in the reward-enhancing effects of ethanol, exploratory analyses suggested that adolescent intermittent ethanol exposure may perhaps also increase sensitivity to the rewarding or appetitive effects of ethanol. Rodents selectively bred for high ethanol consumption show similar ethanol sensitivities (Chester et al, 2006; Eiler et al, 2007; Fish et al, 2012), suggesting that high sensitivity to ethanol reward and low sensitivity to ethanol withdrawal may predict heavy or problematic alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…However, the long-term effects of adolescent ethanol exposure on brain reward function during re-exposure to ethanol in adulthood have not been studied. Interestingly, rodent strains bred for high ethanol consumption exhibit heightened sensitivity to the reward-enhancing effects of ethanol and blunted sensitivity to the anhedonia associated with ethanol withdrawal (Chester et al, 2006; Eiler et al, 2007; Fish et al, 2012). These findings suggest that heightened sensitivity to the reward-enhancing effects of ethanol or blunted sensitivity to the anhedonia of ethanol withdrawal accompany and may predict increased ethanol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Several drugs of abuse, including alcohol (Carboni et al, 2000) and cocaine (Epping-Jordan et al, 1998), increase extracellular dopamine levels in the BNST. In addition, intracerebral self-stimulation (ICSS) in the BNST supports operant behavior in alcohol-preferring (P) but not nonalcohol-preferring (NP) rats (Eiler et al, 2007) and is a substrate for heightened sensitivity to the anxiogenic effects of corticotropin-releasing factor in Marchigian AlcoholPreferring (msP) rats (Ciccocioppo et al, 2003a). Additionally, elevations in BNST excitatory transmission have been linked to behavioral responses reinforced by cocaine and food, but not to either reward when given passively (Dumont et al, 2005).…”
Section: Neuroplasticity In Mglurmentioning
confidence: 99%